2021
DOI: 10.1097/bsd.0000000000001282
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Hidden Blood Loss in Lumbar Disk Herniation Patients With Percutaneous Endoscopic Transforaminal Discectomy and Influencing Factors

Abstract: Objectives: This study aimed to evaluate hidden blood loss (HBL) and its influencing factors in lumbar disk herniation (LDH) patients treated with percutaneous endoscopic transforaminal discectomy (PETD).Summary of Background Data: PETD is a minimally invasive spine surgery and is widely used to treat LDH. It is generally believed that there is less bleeding during PETD. However, HBL during the perioperative period is always ignored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
0
7
1
Order By: Relevance
“…Hypertension( p = 0.002) and Diabetes( p < 0.001) were a positive influencing factor of hidden blood loss, which were contrary to the findings of Man Hu et al [ 18 ]. The author believes that this discrepancy may stem from the surgical approach (Percutaneous endoscopic transforaminal discectomy (PETD) for lumbar disc herniation no bone tissue damage and minimal soft tissue damage).…”
Section: Discussioncontrasting
confidence: 88%
“…Hypertension( p = 0.002) and Diabetes( p < 0.001) were a positive influencing factor of hidden blood loss, which were contrary to the findings of Man Hu et al [ 18 ]. The author believes that this discrepancy may stem from the surgical approach (Percutaneous endoscopic transforaminal discectomy (PETD) for lumbar disc herniation no bone tissue damage and minimal soft tissue damage).…”
Section: Discussioncontrasting
confidence: 88%
“…To date, the most common complications occurring after arthroscopic surgery may be related to hidden blood loss, which is to rule out significant blood loss during surgery and postoperative drainage volume, as the part of the body’s hidden loss of blood volume. Hidden blood loss is generally associated with hematocele in the joint space, interstitial hematocele, hemolysis, and stress gastrointestinal bleeding leading to hemoglobin loss ( 9 ). However, there are few reports on the factors behind hidden blood loss after knee arthroscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there are several reports on the relationship between total operational time and perioperative HBL. A retrospective study reported that patients' HBL increased in direct proportion to the length of the surgery ( 26 ). Another retrospective cohort analysis discovered a significant correlation between the quantity of HBL and the overall operating time ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, APTT is another coagulation activity indicator, and its reduction is regarded as activation of the endogenous coagulation pathway. Most of the literature reported that pre-operative APTT was not correlated to patients' HBL during the perioperative period ( 8 , 26 ). In contrast, some clinical research has identified APTT as a positive risk factor for HBL in TBF patients, and increased APTT can promote an increase in HBL, which could be explained by hemolysis ( 6 ).…”
Section: Discussionmentioning
confidence: 99%